Hubungan Ilmu dan Agama dalam Perspektif Imam Al-Ghazali - Maula Sari; Marhaban (At-Tafkir, 2022)
In this study, the author explains how the relationship between science and religion from a fiqh expert, philosopher, and Sufi, namely Imam Al-Ghazali, is of course very important to study. The urgency or purpose of this discussion is to study the division of knowledge according to Al-Ghazali and see the spiritual development of an Imam Al-Ghazali. This paper is expected to make it easier for readers related to science and religion according to Imam Al-Ghazali and a bridge to understand the relationship between science, knowledge and religion according to Imam Al-Ghazali. The research used in this study is a literature study (liberary research) with a descriptive qualitative approach. The result of this discussion is that al-Ghazali's spiritual development is divided into three, namely before uzlah, during uzlah, and after uzlah. In his thinking al-Ghazali did not distinguish between knowledge and knowledge, both are the same. Therefore, al-Ghazali's concept is personal that the relationship between creator and creature is never united, only the closeness of creature and creator through piety. Al-Ghazali's religion and science are both objects that can be studied or studied and do not conflict with each other.